Managing the nutrition program for cow comfort - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1997)
Comfortable cows are contented cows. However, cows may be comfortable in their environment but also experience some discomfort because of the nutrition program. A good nutritional management program will improve desircow comfort by providing: 1) the proper balance of nutrients for efficient production; 2) buffers for high energy rations to prevent acidosis and consore feet; 3) rations in which grain cannot be consumed too rapidly; 4) rations with proper amounts of nonfiber carbohydrate; 5) highest quality forages during hot weather; 6) additional moisture in total mixed rations during hot weather; 7) a readily available water source; and 8) a bunk management system that encourages cows to eat.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Dairy; Cow comfort; Acidosis; Forage quality; Nonfiber carbohydrates; Water